Feasibility of the transportation options of renewable hydrogen for moderate distances: Insights from a remote production in Finland - Satu Lipiäinen; Esa Vakkilainen (Energy Conversion and Management: X, 2025)
Renewable hydrogen production resources are frequently distant from the users, creating a need for transportation. The purpose of this study is to compare the economics of different transportation options for moderate distances (∼200 km). The included options are hydrogen transportation using a pipeline, a truck, or a train compared to electricity transmission via grid. The results suggest that transportation costs are 0.1–2.9 €/kgH2. Thus, a large portion of renewable hydrogen price could be from transportation. The optimal transportation option depends on the volumes of hydrogen. In large-scale transportation, a pipeline option has a minor effect on the total hydrogen costs. However, both scaling up the production of electricity and hydrogen as well as building the pipeline are large investments and building times are long. Even though the studied transportation distance was short, the need for transportation can cause notable additional costs in comparison to production site with a more optimal location.